A new species of Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from Kamchatka Peninsula ... - Ryabukhin, A. S. (Zenodo, 2015)
Ryabukhin, A. S. (2015): A new species of Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from Kamchatka Peninsula. Far Eastern Entomologist 295: 8-11, DOI: http://doi.org/10.5281/zenodo.10084234 ...